Ships and shipwrecks of the late Tudor Dynasty - Taylor, James D., 1958- (Algora Publishing, 2022)
"In the 1500s, British ships plied the seas laden with precious spices, Spanish silver, war matériel, and adventurous souls. Many went to the bottom, leaving only tantalizing hints, sparse records and a few legends. This unique collection of logs, data and narratives from 1547-1603 brings them to life"--